Evaluation of the pharmacokinetic drug-drug interaction between the antiretroviral agents fostemsavir and maraviroc: a single-sequence crossover study in healthy participants. Issue 1 (9th December 2021) - Wire, Mary Beth; Magee, Mindy; Ackerman, Peter; Llamoso, Cyril; Moore, Katy
Abstract : Background: Fostemsavir is an oral prodrug of temsavir, a first‐in‐class attachment inhibitor that binds HIV‐1 gp120, preventing initial HIV attachment and entry into host immune cells. Objective: The pharmacokinetic interaction was determined between temsavir and maraviroc, a CCR5 allosteric inhibitor indicated for CCR5-tropic HIV-1 that may be co-administered with fostemsavir as part of combination antiretroviral therapy in heavily treatment-experienced adults with multidrug-resistant HIV-1 infection. Methods: This was a Phase 1, open-label, single-sequence, 3-period crossover study evaluating the effect of fostemsavir on maraviroc pharmacokinetics and the effect of maraviroc on temsavir pharmacokinetics (ClinicalTrials.gov, NCT02480894). Fourteen healthy participants received fostemsavir 600 mg twice daily (BID) for 4 days in Period 1 (followed by a 3-day washout), maraviroc 300 mg BID for 5 days in Period 2, and fostemsavir 600 mg BID with maraviroc 300 mg BID for 7 days in Period 3. Study drugs were administered orally with a standard meal. Results: Following fostemsavir and maraviroc co-administration, maraviroc area under the plasma concentration-time curve over the dosing interval (AUCτ ) increased 25% (from 1914 to 2382 ng.h/mL) and maraviroc plasma concentration at the end of the dosing interval (Ctrough ) increased 37% (from 36.5 to 49.9 ng/mL), but there was no change in maximum observed concentration (Cmax ). Following fostemsavir and maraviroc co-administration, temsavir AUCτ and Cmax increased 10-13% and Ctrough decreased 10%. Conclusions: Co-administration of fostemsavir and maraviroc did not result in clinically relevant changes in maraviroc or temsavir exposure. Fostemsavir and maraviroc may be co-administered without dose adjustment of either antiretroviral agent.